2014
DOI: 10.1007/s12298-013-0217-z
|View full text |Cite
|
Sign up to set email alerts
|

Hairy root induction and plant regeneration of medicinal plant Dracocephalum kotschyi

Abstract: An efficient hairy root induction system for an important endangered medicinal plant, Dracocephalum kotschyi, was developed through Agrobacterium rhizogenesmediated transformation by modifying the co-cultivation medium using five bacterial strains, A4, ATCC15834, LBA9402, MSU440, and A13 (MAFF-02-10266). A drastic increase in transformation frequency was observed when a Murashige and Skoog medium lacking NH 4 NO 3 KH 2 PO 4, KNO 3 and CaCl 2 was used, resulting in hairy root induction frequencies of 52.3 %, 69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 24 publications
5
17
0
Order By: Relevance
“…Similar results have been drawn in another study on the bottle gourd that explains BA is essential for shoot bud formation (Saha et al 2007). In our experiments, shoot formation was not detected on the hormone-free medium, which is in consistence with the results obtained by Pogostemon cablin and Dracocephalum kotschyi (He-Ping et al 2011;Sharafi et al 2014), respectively. In summary, the insertion of native A. rhizogenes T-DNA into the O. vulgare genome worked successfully.…”
Section: Molecular Analysis Of Transgenic Hairy Rootssupporting
confidence: 92%
“…Similar results have been drawn in another study on the bottle gourd that explains BA is essential for shoot bud formation (Saha et al 2007). In our experiments, shoot formation was not detected on the hormone-free medium, which is in consistence with the results obtained by Pogostemon cablin and Dracocephalum kotschyi (He-Ping et al 2011;Sharafi et al 2014), respectively. In summary, the insertion of native A. rhizogenes T-DNA into the O. vulgare genome worked successfully.…”
Section: Molecular Analysis Of Transgenic Hairy Rootssupporting
confidence: 92%
“…Prior studies indicated that vir G expression can be triggered by low levels of PO 4 and proposed that PO 4 deficiency could be a helpful signal to prompt genetic transformation. Similar results were described in transformation by A. tumefaciens in Lilium (36) and genetically transformed root generation of Papaver bracteatum, Nepeta pogonosperma, Dracocephalum kotschyi, and Artemisia aucheri (26,31,34,37). 4 Jundishapur J Nat Pharm Prod.…”
Section: Discussionsupporting
confidence: 78%
“…Sharafi et al (2014a) used liquid inoculation and solid co-cultivation media in absence of macro elements, such as KH 2 PO 4 , NH 4 NO 3 , KNO 3 and CaCl 2 , to transform medicinal plant Dracocephalum kotschyi with high efficiency (31). In another study, Henzi et al (2000) indicated that the usage of acetosyringone and arginine in the agar solidified co-cultivation medium, which revealed major enhancement in transformation rate of Brassica by Agrobacterium (32).…”
Section: Introductionmentioning
confidence: 99%
“…Transformation efficiency can be over 40 % using binary vector (co-transformation of rol gene and target gene) by this protocol. The transgenic hairy roots can be used as explants for plantlet regeneration to obtain stable transgenic plants (Sharafi et al 2013a). …”
Section: Discussionmentioning
confidence: 99%